2004
DOI: 10.1108/13620430410518129
|View full text |Cite
|
Sign up to set email alerts
|

Cynicism and disengagement among devalued employee groups: the need to ASPIRe

Abstract: Despite a renewed interest in processes which help organizations to harness social capital, it is apparent that practical efforts to achieve this rarely focus on employees who are members of low status groups. In large part this is because such employees tend to be skeptical of, and to resist, engagement in intervention programs on the basis of previous adverse experience regarding the benefits achieved and lack of trust. This paper presents evidence that, among hospital staff, work groups who felt they were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…Teicher (1992) has argued that involvement has been used to generate legitimacy for decisions already made by management, while O'Brien et al (2004) have argued that opportunities for involvement are "fundamentally contingent on concern for the bottom line and management prerogative . .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teicher (1992) has argued that involvement has been used to generate legitimacy for decisions already made by management, while O'Brien et al (2004) have argued that opportunities for involvement are "fundamentally contingent on concern for the bottom line and management prerogative . .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nature of the change appears to be significant. O'Brien et al (2004) have suggested that the status of the employees affected by change is important. They argued that organizations have difficulty getting low-status employees to identify with the organization and exert effort on behalf of it.…”
Section: Policy and Practice Implicationsmentioning
confidence: 99%
“…After more than a decade of research this is a prediction that now enjoys a broad base of support – with relevant evidence having been garnered from quantitative and qualitative studies of hospital staff (O'Brien et al ., ), military medics (Peters et al ., ), the Copenhagen climate change conference (Batalha & Reynolds, ), school teachers, students (Reynolds, Subasic, Lee, & Tindall, in press), and even a simulated expedition to Mars (Persaud et al ., ). Our current research also points to the value of AIRing as a clinical procedure that can be used to inform both diagnosis and intervention (e.g., Best et al ., in press; Cruwys, Dingle, et al ., ).…”
Section: Lessons From and For An Applied Social Identity Approach (Asia)mentioning
confidence: 99%
“…In this dimension, the employee may get alienated from or sever her ties with the organization (O'Brien et al, 2004). …”
Section: Behavioral Dimensionmentioning
confidence: 99%